In-situ Observation of Retained Austenite and Residual Stress Evolutions during Tempering of carbonitrided DIN 1.6587 Alloy Steel - Katemi, Richard J.; Epp, Jérémy (Tanzania Journal of Engineering and Technology, 2022)
This paper investigates the evolution of retained austenite and residual stresses during and after tempering of carbonitrided 18CrNiMo7-6 low alloy steel carried out using in-situ X-ray diffraction technique. In this case, two carbonitriding treatments with different surface the retained austenite contents of 20 and 54 mass.-% are investigated. The tempering is carried out in a continuous heating mode to 650 °C as well as in isothermal mode at holding temperature of 170, 240, and 300 °C for 2 hours. During continuous heating at a heating rate of 10 °C/min, the retained austenite started to decompose at 290 °C. On isothermal holding at 170 °C for 2 hours, the retained austenite remained relatively stable at 20 and 54 mass.-% while readily decomposed to less than 5 mass-% on holding at 300 °C. On continuous heating, residual stress in martensite continuously relaxes and reaches full relaxation (0 MPa) at about 400 °C. During isothermal holding, residual stresses in martensite are increasingly relaxed with increasing holding tempering. Further relaxation of residual stresses is observed during cooling whereas a cyclic variation of the residual stresses in the retained austenite could be determined. Keywords: Carbonitriding, retained austenite, residual stresses, tempering, in-situ XRD <table class="MsoNormalTable" style="width: 472.5pt; margin-left: 5.4pt; border-collapse: collapse; mso-yfti-tbllook: 1184; mso-padding-alt: 0cm 5.4pt 0cm 5.4pt;" width="630" border="0" cellspacing="0" cellpadding="0"> This paper investigatesthe evolution of retained austenite and residual stresses during and after tempering of carbonitrided 18CrNiMo7-6 low alloy steel carried out using in-situ X-ray diffraction technique. In this case, two carbonitriding treatments with different surface the retained austenite contents of 20 and 54 mass.-% are investigated. The tempering is carried out in a continuous heating mode to 650 °C as well as in isothermal mode at holding temperature of 170, 240, and 300 °C for 2 hours. During continuous heating at a heating rate of 10 °C/min, the retained austenite started to decompose at 290 °C. On isothermal holding at 170 °C for 2 hours, the retained austenite remained relatively stable at 20 and 54 mass.-% while readily decomposed to less than 5 mass-% on holding at 300 °C. On continuous heating, residual stress in martensite continuously relaxes and reaches full relaxation (0 MPa) at about 400 °C. During isothermal holding, residual stresses in martensite are increasingly relaxed with increasing holding tempering. Further relaxation of residual stresses is observed during cooling whereas a cyclic variation of the residual stresses in the retained austenite could be determined.